Cosmological particle production in a quantum field simulator as a quantum mechanical scattering problem - Schmidt, Christian F.; Parra-López, Álvaro; Tolosa-Simeón, Mireia; Sparn, Marius; Kath, Elinor; Liebster, Nikolas; Duchene, Jelte; Strobel, Helmut; Oberthaler, Markus K.; Flörchinger, Stefan (Physical review, 2024)
The production of quantum field excitations or particles in cosmological spacetimes is a hallmark prediction of curved quantum field theory. The generation of cosmological perturbations from quantum fluctuations in the early Universe constitutes an important application. The problem can be quantum-simulated in terms of structure formation in an interacting Bose-Einstein condensate (BEC) with time-dependent s-wave scattering length. Here, we explore a mapping between cosmological particle production in general (𝐷+1)-dimensional spacetimes and scattering problems described by the nonrelativistic stationary Schrödinger equation in one dimension. Through this mapping, intuitive explanations for emergent spatial structures in both the BEC and the cosmological system can be obtained for analogue cosmological scenarios that range from power-law expansions to periodic modulations. The investigated cosmologies and their scattering analogs are tuned to be implemented in a (2+1)-dimensional quantum field simulator.